Testing weak form of stock market efficiency at the Macedonian stock exchange - Julijana Angelovska (UTMS Journal of Economics, 2018)
The efficient market research to date has focused mostly on the developed stock markets. To be efficient the market needs to be large and liquid, transaction costs should be cheaper than the expected investment strategy profits and Macedonian capital market as a developing market is characterized by low liquidity, shallow trading, large price fluctuations, uninformed investors with access to unreliable information and significant instability. According to these characteristics the aim of this study is to investigate emerging, Macedonian Stock Exchange (MBI10) and test the weak form of efficiency. Tests are performed for daily returns on sample spanning from January 4th 2005 to April 2nd 2018. The application of Random Walk Model and GARCH (1,1) model provides evidence that Macedonian Stock Market is not weak form efficient. The evidence of stock market inefficiency has implications. Negative implication of such inefficiency can be found in disturbing the allocation of national resources for development projects. Of course, there is positive implication as well that provides incentives for new financial products. Creation of new innovative financial products can produce material that will move the stock market towards efficiency in the long run.
Keywords: G15; C32; G14; 330; random walk model; GARCH (1; 1); stock returns; investor rationality; capital market